Exploring synthetic strategy for stabilizing nickel-rich layered oxide cathodes through structural design - Wu, Qiang; Wang, Baofeng (Chinese chemical letters, 2024)
A combined strategy of heterogeneous nucleation and Kirkendall effect for constructing nickel-rich layered oxide materials with unique morphology and element distribution is proposed. The as-prepared LiNi0.96Al0.04O2 exhibits excellent long-term electrochemical stability. [Display omitted]